2006
DOI: 10.1021/jf052243m
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Lipoxygenase Activity Induces Greater Loss of Carotenoids than Vitamin E during Breadmaking

Abstract: The current study was undertaken to provide solutions to optimize the unsaponifiable antioxidants content of bread. We report a complete description of changes in wheat carotenoids and vitamin E content from grain to bread and highlight the most important processing steps affecting their level in wheat bread. Major carotenoids losses occurred during kneading. A close correlation (r(2) = 0.97; P = 0.05) was found between carotenoid pigment losses and lipoxygenase (LOX) activity, both parameters depending on whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
108
1
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(122 citation statements)
references
References 22 publications
(22 reference statements)
11
108
1
2
Order By: Relevance
“…In common wheat, high LOX activity is traditionally employed in white bread processing, because it improves bread color and dough rheology (Faubion and Hoseney, 1981). However, recent investigations show that high LOX activity during breadmaking reduces the nutritional quality of bread owing to the degradation of carotenoids (Leenhardt et al, 2006). In this work, we found that TaLOX1 and TaLOX2 were expressed in the developing grains of both CS and Xiaoyan 54, and their transcript levels increased from three to four WPA.…”
Section: Potential Contribution Of Talox1 and Talox2 To Lox Activity mentioning
confidence: 47%
“…In common wheat, high LOX activity is traditionally employed in white bread processing, because it improves bread color and dough rheology (Faubion and Hoseney, 1981). However, recent investigations show that high LOX activity during breadmaking reduces the nutritional quality of bread owing to the degradation of carotenoids (Leenhardt et al, 2006). In this work, we found that TaLOX1 and TaLOX2 were expressed in the developing grains of both CS and Xiaoyan 54, and their transcript levels increased from three to four WPA.…”
Section: Potential Contribution Of Talox1 and Talox2 To Lox Activity mentioning
confidence: 47%
“…It is interesting to note that the flavor changes in bread supplemented with DFF might be correlated to the high levels of phenolic compounds; this finding has agreement with Menon et al (2015). According to the researches of Leenhardt et al (2006) and Holtekjølen et al (2008) bioactive compounds existing in flour might be destroyed or lost during baking. In this study, the TFC in both the flour and breads of DFF-WF composite was measured and expressed as mg of rutin equivalents (RE)/g (g) DW.…”
Section: Chemical Composition Of Dff-wf Composite Breadsmentioning
confidence: 71%
“…The TFC ranked for both flour and bread samples in descending order, as follows: 20 % DFF, 15 % DFF, 10 % DFF, 5 % DFF and 0 % DFF (control); whatever the substitution ratio, the flavonoids content in the flours was higher than in the breads. Processing stages including mixing, kneading, and heating affects the flavonoids content of the bread (Holtekjølen et al 2008;Leenhardt et al 2006).…”
Section: Chemical Composition Of Dff-wf Composite Breadsmentioning
confidence: 99%
“…Luteín je v zrnách pšenice prítomný v obalových vrstvách, endosperme a zárodku, čo predstavuje približne 80 -90 % celkového obsahu karotenoidov. Podieľa sa na svetlo krémovej až žltej farbe pšeničných finálnych výrobkov (Leenhardt et al, 2006a).…”
unclassified